SISTEM INFORMASI MONITORING TARGET CAPAIAN PEMBINAAN AL-QUR’AN DI WILAYAH PONDOK PESANTREN NURUL JADID BERBASIS WEB - Syafiih, M .; AHZ, Nadiyah; Arifin, Nur Harima Indah (Journal of Advanced Research in Informatics, 2023)
The target achievement of the students' Al-Qur'an development is an activity program carried out in each area of the Nurul Jadid Islamic Boarding School, as for the material studied in Al-Qur'an development is Tajweed Science, the target achievement of the students' Al-Qur'an development is a pesantren and regional program that contains material on the laws of tajweed to be studied thoroughly and completed to the students. However, in the process of managing data on the target achievement of the students' Al-Qur'an coaching, they still use conventional methods. With a coaching system that is still carried out conventionally, it is necessary to have an information system that can facilitate management in managing Al-Qur'an coaching achievement target data. Through the PHP programming language using the CodeIgniter framework and MySQL as a relational database. The purpose of this research is to produce a system or application that is able to process data on the target achievement of students' Al-Qur'an coaching and is able to provide information on the development of students using existing data. The research method used is a qualitative method, the system development technique used is the waterfall method, while data collection is carried out using interview and observation data collection methods. The testing technique uses blackbox. This research produces an information system application for the achievement of students' Al-Qur'an coaching targets, making it easier for Al-Qur'an coordinators and muallim to monitor and manage data on the achievement of students' Al-Qur'an coaching targets and obtain information on the achievement and development of students. Based on the results of testing to users with a questionnaire 82% stated that they strongly agree with the existence of this monitoring information system and also this system is in accordance with what the central Al-Qur'an coordinator expects, namely being able to monitor the target achievement of the students' Al-Qur'an development.